Dendritic cell–epithelial cell crosstalk in the gut. Issue 1 (July 2014) - Rescigno, Maria
Summary: Intestinal epithelial cells are fundamental to maintain barrier integrity and to participate in food degradation and absorption, but they can also decipher signals coming from the outside world and 'educate' the immune system accordingly. In particular, they interact with dendritic cells (DCs) and other intraepithelial immune cells to drive tolerogenic responses under steady state, but they can also release immune mediators to recruit inflammatory cells and to elicit immunity to infectious agents. When these interactions are deregulated, immune disorders can develop. In this review, we discuss some important features of epithelial cells and DCs and their fruitful interactions.